SINTESIS BIODIESEL DENGAN METODE IMPREGNASI CaO-AlCl3 MENGGUNAKAN BAHAN BAKU MINYAK JELANTAH - St Annisa Gani Rachim (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
The background is that in the biodiesel production process, the use of CaO catalyst can react with CO2 and H2O to form Ca(OH)2 in the air, causing its catalytic activity to become less effective. Therefore, modification of the CaO catalyst is needed by using the method of impregnating the CaO catalyst with AlCl3 catalyst.. Therefore, modifying the CaO catalyst with the AlCl3 catalyst using the impregnation method is necessary. This process can prevent deactivation, increase catalytic activity and surface area, and prevent soap formation during biodiesel production. This study aims to determine the presence of alkyl ester groups and the effectiveness and percentage of biodiesel in the resulting product. The research method begins with purifying used cooking oil, impregnating CaO with AlCl₃, and synthesizing biodiesel through transesterification using the oil as the raw material. The reaction was performed at 70 °C with a 3% catalyst concentration by weight of the oil. The products were identified using Fourier transform infrared spectroscopy (FTIR). The results showed the presence of ester groups with a biodiesel conversion value of 87.84%. The study concluded that biodiesel produced using the impregnated catalyst method is effective because the obtained value is close to the ASTM D6751 standard. Keywords: Biodiesel, impregnation, CaO-AlCl3 catalyst, transesterification, waste cooking oil